Black Hole or Black Gold? The Impact of Oil and Gas Prices on Indonesia's Public Finances - Agustina, Cut Dian R.D.; Arze del Granado, Javier; Bulman, Tim; Fengler, Wolfgang; Ikhsan, Mohamad (World Bank, Washington, DC, 2012)
Indonesia's oil revenues and fuel subsidies dominate the nation's economic policy agenda. This paper estimates the impact of higher international oil prices on the Indonesian government's fiscal position in 2008 and beyond. It analyzes the interactions between government revenues and expenditures, as well as international oil prices, energy subsidies, and inter-governmental transfers. Looking at the impact of oil prices over US$100 per barrel, the paper presents five main findings. First, despite record high oil prices, the government's oil and gas revenues have been decreasing relative to non-oil and gas revenues since 2001. Second, fuel subsides will reach record levels in 2008 while electricity subsidies have been increasing even faster. Third, the paper finds that most of the fuel subsidy that directly benefits households goes to the richest 20 percent. Fourth, even at levels above US$100 per barrel, the government receives more revenues from oil and gas than it spends on energy subsidies. However, due to significant revenue-sharing with sub-national governments, high oil prices are net-negative for the central government, while they create fiscal windfalls for many regions. Finally, the oil sector's positive impact on Indonesia's public finances declines as oil prices rise, because subsidies and other expenditures outgrow oil and gas revenues.